TECHNOSTRESS DAN PENGARUHNYA TERHADAP KINERJA DOSEN PERGURUAN TINGGI DI INDONESIA - Amalia, Wia Rizqi; Rimayanti; Syahdan, Saifhul Anuar (LPPM Universitas Nias Raya, 2023)
The COVID19 pandemic has brought major changes in the learning and teaching process in Universities. Then, lecturers began to using technology in learning process intensely. Further, this study examines the existence of stress by lecturers in using technology (technostress), and how it affects their performance. The results of a survey of 123 lecturers at Universities in Indonesia show that technology affects performance in both positive and negative ways. Technostress indicators, called techno-overload, techno-insecurity, and techno-uncertainty have an effect on performance, while techno-invasion and techno-complexity have no effect on performance.